Serum Sphingosine-1-phosphate level and peritonitis in peritoneal dialysis patients. Issue 1 (1st January 2020) - Bai, Qiong; Guo, Hong-Xia; Su, Chun-Yan; Han, Qing-Feng; Wang, Tao; Tang, Wen
Abstract: Background: Given the important role of Sphingosine-1-phosphate (S1P) in maintaining the hemostasis in intestinal barrier function and regulation of inflammation and immune, we hypothesize that S1P might be a biomarker to predict peritonitis in peritoneal dialysis (PD) patients. Methods: In this case-control study, 78 stable, continuous ambulatory peritoneal dialysis patients were enrolled and followed for the episode of PD associated peritonitis. Patients were divided into two groups by whether or not they had peritonitis during follow-up: non-peritonitis ( n = 65) and peritonitis ( n = 13) group. S1P was analyzed by enzyme-linked immunosorbent assay. Logistic regression analysis was used to assess factors associated with peritonitis. The variables identified by univariable regression models ( p < 0.1) were further selected into the multivariable logistic regression model to determine whether they could independently affect peritonitis. Results: Patients with peritonitis had a lower level of S1P than that of patients without peritonitis (1.3 ng/mL IQ 0.8, 3.6 ng/mL vs. 2.8 ng/mL IQ 1.5, 5.4 ng/mL, p = 0.018). The peritonitis group had lower serum albumin, lower blood leukocyte, lower hemoglobin and lower platelet count as compared to the non-peritonitis group. Logistic regression analysis showed that S1P (OR = 0.381, 95% CI = 0.171–0.848, p = 0.018), blood leukocyte count (OR = 0.438, 95% CI = 0.207–0.925, p = 0.030), and serum albumin (OR = 0.732, 95% CI = 0.556–0.962, p = 0.025) were independent factors associated with peritonitis in the present PD population. Conclusion: Our study showed that S1P was an independent determinant of subsequent peritonitis in PD patients. S1P might serve as a biomarker to predict peritonitis in PD patients.